A Highly Responsive Self‐Driven UV Photodetector Using GaN Nanoflowers. (10th April 2017) - Aggarwal, Neha; Krishna, Shibin; Sharma, Alka; Goswami, Lalit; Kumar, Dinesh; Husale, Sudhir; Gupta, Govind
Abstract : The rising demand for optoelectronic devices to be operable in adverse environments necessitates the sensing of ultraviolet (UV) radiation. Here, a self‐driven, highly sensitive, fast responding GaN nanoflower based UV photodetector is reported. By developing unique structures, the light absorption increases efficiently and a maximum responsivity of 10.5 A W −1 is achieved at 1 V bias. The reported responsivity is the highest among the GaN UV photodetectors on Si substrates and commercially available Si‐based UV photodetectors. Under self‐driven condition, the photodetector exhibits very low dark current (≈nA) with a very high responsivity (132 mA W −1 ) and detectivity (2.4 × 10 10 Jones). A remarkably high light‐to‐dark current ratio of ≈260 signifies extremely high photodetection gain compared to planar GaN‐based photodetectors. The self‐driven and biased photodetector device yields highly stable rise and decay time response. A model based on band theory elucidates the origin of self‐driven photodetectors. Implementation of the innovative growth design structures assures an exceptionally high sensitivity toward UV signal, which is capable of substituting the existing technology of UV photodetectors. High responsivity and detectivity from devices based on the GaN nanoflower‐like structure with the advantage of high surface/volume ratio can have numerous applications in fabrication of nanoscale optoelectronic high performance devices such as self‐driven UV photodetectors. Abstract : A GaN nanoflower‐based UV photodetection device with detectivity ≈10 10 Jones and a dark current on the nano‐Ampere scale is demonstrated. Compared to thin films, the nanostructures offer an extremely stable and responsive photodetector yielding a highest photoresponsivity of 10.5 A W −1 under 1 V applied bias. This may be advantageous for the development of nanoscale optoelectronic high‐performance devices.